Wie verändern Hybrid-DRGs („diagnosis related groups“) die deutsche Urologie?: eine Umfrage und Potentialanalyse - Reimold, Philipp; Groeben, Christer; Borkowetz, Angelika; Eisenmenger, Nicole; König, Frank; Leitsmann, Marianne; Witzsch, Ulrich; Müller, Markus; Schöne, Markus; Schultz-Lampel, Daniela; Fisch, Margit; Kollenbach, Peter; et al. (Die Urologie, 2025)
Background The introduction of hybrid DRGs on 1 January 2024 is intended to create incentives to perform inpatient urology services, e.g., ureterorenoscopy (URS), on an outpatient basis. The effects on the reality of care are currently unclear. Objectives The aim of the survey was to gather an opinion on the introduction of hybrid DRGs in urology and to analyze initial practical experiences and future prospects. Materials and methods In a Germany-wide online survey conducted between May and July 2024, 32 questions were asked about patient care, further training and other indications, among other things. In addition, an assessment of the outpatient potential for URS for ureteral and kidney stones and hydrocele resections was requested. Results A total of 364 urologists responded to the survey: 54.5% were in private practice and 45.5% worked in hospitals. 91.1% were active surgeons. The concept of hybrid DRGs was rated positively by 34% of those working in surgery, but 68% saw no relief in their everyday work. 51% expressed concerns about the negative impact on further training. The proportion of URS performed on an outpatient basis in 2023 was 21% (ureteral stones) and 11% (kidney stones), with a long-term potential increase of up to 33%. Two thirds of hydrocele resections were already performed on an outpatient basis, and 74% of respondents considered these to be billable in a hybrid DRG. Conclusion The survey shows a differentiated opinion on hybrid DRGs in urology, but the sample only comprises around 6% of urologists in Germany. It would make sense to repeat the survey at a later date in order to evaluate developments in practical use.